Effect of mulching treatments on growth, water relations and fruits yield of sapota (Achras sapota) - REDDY, Y T N; KHAN, M M (The Indian Journal of Agricultural Sciences, 2013)
The soil-moisture status in different soil depths was significantly increased by different mulches and 400 gauge black polythene mulch recorded the maximum soil-moisture percentage. All the mulching treatments significantly increased the relative water contect and the effect was more pronounced with 400 gauge black polythene mulch. Black polythene mulch increased the transpiration with reduced stomatal resistance. Mulching treatments. Maximum fruits yield was obtained with 200 gauge followed by 400 gauge black polythene mulch. The cumulative fruit yields were maximum (134.6 kg/plant) with 200 gauge black polythene film although the difference were non-significant among the different mulching treatments. The mulching treatments were not effective in increasing the plant height, plant girth and trunk cross sectional area.